2016
DOI: 10.1002/anie.201604329
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalyzed N‐Desulfonylative Amination versus N‐to‐O 1,5‐Sulfonyl Migration: A Versatile Approach to 1‐Azabicycloalkanes

Abstract: Valuable 1-azabicycloalkane derivatives have been synthesized through a novel gold(I)-catalyzed desulfonylative cyclization strategy. An ammoniumation reaction of ynones substituted at the 1-position with an N-sulfonyl azacycle took place in the presence of a gold cation by intramolecular cyclization of the disubstituted sulfonamide moiety onto the triple bond. Depending on the size of the heterocyclic ring and substitution of the substrates, two unprecedented forms of nucleophilic attack on the sulfonyl group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…They were then submitted to the conditions we developed for the gold-catalyzed cycloisomerization-sulfonyl migration reaction and various gold catalysts were briefly surveyed. Although the Gagosz catalyst (PPh 3 AuNTf 2 ) gave good results for the formation of dihydropyrrolizines 6 , JohnPhosAuNTf 2 proved to be more efficient with acyclic as well as cyclic substrates 1 (Scheme 3). Within 5-10 minutes, they were converted to the expected sulfonylated pyrroles 2a-f in high yields (80-93%).…”
Section: Scheme 2 Suzuki-miyaura Palladium Coupling Of N-heteroaryl mentioning
confidence: 99%
“…They were then submitted to the conditions we developed for the gold-catalyzed cycloisomerization-sulfonyl migration reaction and various gold catalysts were briefly surveyed. Although the Gagosz catalyst (PPh 3 AuNTf 2 ) gave good results for the formation of dihydropyrrolizines 6 , JohnPhosAuNTf 2 proved to be more efficient with acyclic as well as cyclic substrates 1 (Scheme 3). Within 5-10 minutes, they were converted to the expected sulfonylated pyrroles 2a-f in high yields (80-93%).…”
Section: Scheme 2 Suzuki-miyaura Palladium Coupling Of N-heteroaryl mentioning
confidence: 99%
“…Importantly, water, alcohols and indoles were all competent nucleophiles in this process. Recently it was shown that phenols on the other hand resulted in desulfonylation of intermediate 28 to give azabicyclo[3.2.0]alkane derivatives …”
Section: Auto‐tandem Catalysis Approaches To Heterocyclesmentioning
confidence: 99%
“…Recently it was shown that phenols on the other hand resulted in desulfonylation of intermediate 28 to give azabicyclo[3.2.0]alkane derivatives. [23] Scheme 7. Gold-catalysed ATC approach to N-sulfonylpyrroin-4-ones.…”
Section: -Membered Ringsmentioning
confidence: 99%
“…The so obtained GBB product imidazo[1,2- a ]pyridine 4a bearing an amino group and an acetylene unit may then undergo a sequential 6- exo -dig cyclization/retro-ene reaction to form the desired imidazo[1,2- a ]pyridine-fused isoquinoline 6a . The cyclization reaction could be realized with the aid of silver or gold catalysts [ 51 52 ].…”
Section: Resultsmentioning
confidence: 99%